A incidência da lavagem de dinheiro na regulação do mercado de obras de arte e antiguidades brasileiro - Medeiros, Pedro Lucas Campos de (2020)
The analysis of the economic system as a scenario for the spread of criminal practices is a challenge for the Brazilian legal system. In this context, the crime of money laundering stands out in terms of the need to improve internal control through institutions and the strengthening of legislation to combat criminal agents and organizations that operate in the proliferation of this crime. Through this problem, it becomes necessary to analyze the incidence of money laundering in specific market sectors that criminal organizations use as a scenario for the proliferation of this illegal practice, as is the case in the art market. Thus, this research proposes to analyze the development of Brazilian legislation to control and prevent money laundering through works of art, antiques and collectors' objects, observing the improvement of legal instruments of internal control, as well as the first databases issued through the Register of Traders of Works of Art and Antiques (Cnart) of the National Institute of Historical and Artistic Heritage (Iphan). Therefore, we seek to answer the following problem: what are the current results of Brazilian anti-laundering legislation in the regulation of the art market? It is a research carried out through the deductive method, starting from general assumptions about the concept, characteristics and criminological definition of money laundering, covering the development of the art market in Brazil, in order to reach the specific legislation, the performance of the institutions and databases on the topic.